2004
DOI: 10.1111/j.1479-828x.2004.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of botulinum toxin type A in the treatment of chronic pelvic pain associated with spasm of the levator ani muscles

Abstract: There is evidence from the present pilot study suggesting that women with pelvic floor muscles hypertonicity and pelvic pain may respond to BOTOX injections into the pelvic floor muscles. Further research into this novel treatment of chronic pelvic pain is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 13 publications
1
137
1
7
Order By: Relevance
“…Studies utilizing transvaginal injection of trigger points are limited but predominantly include the attempts at relief of levator ani muscle spasm using botulinum Neurourology and Urodynamics DOI 10.1002/nau toxin A, utilizing the theory that paralysis of a spastic levator muscle will relieve pain [Romito et al, 2004;Fitzgerald et al, 2005;Thomson et al, 2005]. A study by Jarvis et al [2004] showed signi¢cant improvement on VAS in 12 women with the use of botulinum toxin A using three di¡erent dilutions [Thomson et al, 2005]. Other treatments with pelvic £oor muscle rehabilitation or electrogalvanic stimulation have also shown promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing transvaginal injection of trigger points are limited but predominantly include the attempts at relief of levator ani muscle spasm using botulinum Neurourology and Urodynamics DOI 10.1002/nau toxin A, utilizing the theory that paralysis of a spastic levator muscle will relieve pain [Romito et al, 2004;Fitzgerald et al, 2005;Thomson et al, 2005]. A study by Jarvis et al [2004] showed signi¢cant improvement on VAS in 12 women with the use of botulinum toxin A using three di¡erent dilutions [Thomson et al, 2005]. Other treatments with pelvic £oor muscle rehabilitation or electrogalvanic stimulation have also shown promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Sherin et al en un estudio piloto tratan con inyecciones de bó tox a 12 mujeres con dolor pé lvico cró nico asociado con espasmo del elevador del ano. Obtienen resultados esperanzadores al conseguir alivio del dolor y disminuir el hipertonicidad 48,49 . Otros autores solo recomiendan la toxina cuando han fracasado otras medidas terapéuticas más sencillas como la aguja seca 50 .…”
Section: Infiltraciones Con Toxina Botulínicaunclassified
“…Podem ser efetivos tanto no diagnóstico como no tratamento de alguns casos de hiperalgesia pós-cirurgia pélvica ou trauma 27 . A dor crônica por espasmo de músculos do assoalho pélvico pode ser tratada também por bloqueio anestésico local, injeção de toxina botulí-nica, fi sioterapia ou eletro-estimulação [45][46][47][48][49] .…”
Section: Tratamentounclassified